Validation of the Vertical Facial Growth Screening Test. (October 2019) - Calvo-Henriquez, Christian; Martins-Neves, Silvia; Martinez-Capoccioni, Gabriel; Neves-Leal, Daniela; Ruano-Ravina, Alberto; Faraldo-García, Ana; Lowy-Benoliel, Alejandro; Martin-Martin, Carlos
Background. Vertical facial growth has a high prevalence. Nonspecialized professionals have shown low sensitivity to identify patients at risk. In the face of this difficulty, we designed and validated a screening checklist for vertical facial growth. Methods. A multidisciplinary team of 5 members developed the Vertical Facial Growth Screening Test. A sample of 160 evaluations was obtained. We consider as the gold standard the evaluation of 2 specialists in dentofacial orthopedics. Results. Consistency measured with Cronbach α was .675 for 10 items. Test-retest reliability was .956. The interobserver concordance was .886. The receiver operating characteristic curve has .987 area under the curve. Conclusion. This is the first study to design and validate a screening checklist for vertical facial growth for nonexpert evaluators. We think that given its good performance, ease of use, inexpensiveness, and availability, the test could be useful for nontrained professionals dealing with children.